Four walls and a roof : the complex nature of a simple profession - Graaf, Reinier de, 1964- (Cambridge, Massachusetts : Harvard University Press, 2017)
Architecture, we like to believe, is an elevated art form that shapes the world as it pleases. Four Walls and a Roof challenges this notion, presenting a candid account of what it is really like to work as an architect, buffeted by external forces that make a mockery of any pretense to visionary authority. Reinier de Graaf draws on his own tragicomic experiences in the field to reveal the world of contemporary architecture in vivid snapshots. He takes us from suburban New York to the rubble of northern Iraq, from the corridors of wealth in London, Moscow, and Dubai to garbage-strewn wastelands that represent the demolished hopes of postwar social housing. We meet oligarchs determined to translate ambitions into concrete and steel, developers for whom architecture is mere investment, and the layers of politicians, bureaucrats, consultants, and mysterious hangers-on who lie between any architectural idea and the chance of its execution. He introduces us to histories of modern architecture that determine--at least as much as individual inspiration--what architects design. And he questions the hubris of those who believe they are the solution to the overwhelming problems of booming megacities. Perhaps the most important myth de Graaf debunks is success itself. To achieve anything, architects must serve the powers they strive to critique, finding themselves in a perpetual conflict of interest. Together, he shows, architects, developers, politicians, and consultants form an improvised world of conflict and compromise that none alone can control.--
Includes bibliographical references.
Keywords: Architectural practice; Architecture